2008
DOI: 10.1143/jjap.47.6337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Added Metallic Elements in Ag-Alloys on Properties of Indium–Tin-Oxide/Ag-Alloy/Indium–Tin-Oxide Transparent Conductive Multilayer System

Abstract: Results on the optical characterisation of copper deep acceptors throughout the alloy composition range (0 < x < 1) of GaAs, -,P, are reported. A comparison of the hole photoionisation spectra for different compositions, measured by the transient photocapacitance technique. reveals a broadening effect near the threshold which is interpreted in terms of random alloy effects on the deep level. An approximately linear variation of the hole photoionisation threshold with composition is found.t O n sabbatical leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Thus, Ag−Pd−Cu (APC) alloy films has gained interest as an attractive alternative to pure Ag coatings due to their high electrical stability and resilience toward agglomeration, even when subjected to high relative humidity environments. 4,26 Jeong et al 27 demonstrated that an APC alloy (Pd and Cu content of 0.9 and Cu 1.7 at. %, respectively) exhibited superior resistance to agglomeration and excellent adhesion to the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, Ag−Pd−Cu (APC) alloy films has gained interest as an attractive alternative to pure Ag coatings due to their high electrical stability and resilience toward agglomeration, even when subjected to high relative humidity environments. 4,26 Jeong et al 27 demonstrated that an APC alloy (Pd and Cu content of 0.9 and Cu 1.7 at. %, respectively) exhibited superior resistance to agglomeration and excellent adhesion to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kim et al 28 showed how an APC layer placed between bottom and top oxide layers can efficiently reduce diffusion of Ag atoms. Even tough APC in OMO structure has been studied in the past, 4,23,28,29 there are only few studies focusing on the threshold thickness, i.e., the thickness limit below the percolation threshold or, in other words, the lower limit at which metal islands rather than a continuous metallic film is achieved. 22 In this work, we show that controlled addition of oxygen, in a reactive magnetron process, enables the fabrication of smooth, ultrathin 5 nm thick continuous APC:O films.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, Ag was used as the metal layer because of its high conductivity and low‐extinction coefficient in the visible range. From these approaches, the low‐sheet resistance and high transmittance of such a multilayer system have been reported as satisfactory 7–9. However, it is reported that the electrical resistivity increased and the transmittance decreased as the temperature increased due to the agglomeration of the Ag film 8–11.…”
Section: Introductionmentioning
confidence: 99%